Detection of New H5N1 High Pathogenicity Avian Influenza Viruses in Winter 2021–2022 in the Far East, Which Are Genetically Close to Those in Europe - Isoda, Norikazu; Onuma, Manabu; Hiono, Takahiro; Sobolev, Ivan; Lim, Hew; Nabeshima, Kei; Honjyo, Hisako; Yokoyama, Misako; Shestopalov, Alexander; Sakoda, Yoshihiro (Viruses, 2022)
Many high pathogenicity avian influenza (HPAI) cases in wild birds due to H5N1 HPAI virus (HPAIV) infection were reported in northern Japan in the winter of 2021–2022. To investigate the epidemiology of HPAIVs brought to Japan from surrounding areas, a genetic analysis of H5 HPAIVs isolated in northern Japan was performed, and the pathogenicity of the HPAIV in chickens was assessed by experimental infection. Based on the genetic analysis of the hemagglutinin gene, pathogenic viruses detected in northern Japan as well as one in Sakhalin, the eastern part of Russia, were classified into the same subgroup as viruses prevalent in Europe in the same season but distinct from those circulating in Asia in winter 2020–2021. High identities of all eight segment sequences of A/crow/Hokkaido/0103B065/2022 (H5N1) (Crow/Hok), the representative isolates in northern Japan in 2022, to European isolates in the same season could also certify the unlikeliness of causing gene reassortment between H5 HPAIVs and viruses locally circulating in Asia. According to intranasal challenge results in six-week-old chickens, 50% of the chicken-lethal dose of Crow/Hok was calculated as 104.5 times of the 50% egg-infectious dose. These results demonstrated that the currently prevalent H5 HPAIVs could spread widely from certain origins throughout the Eurasian continent, including Europe and the Far East, and implied a possibility that contagious viruses are gathered in lakes in the northern territory via bird migration. Active monitoring of wild birds at the global level is essential to estimate the geographical source and spread dynamics of HPAIVs.